Penerapan Pedoman Umum Gizi Seimbang dalam Pemeliharaan Kesehatan Jantung pada Ibu Peserta dan Bukan Peserta Klub Jantung Sehat di Kalurahan Pleret Bantul Yogyakarta - Rizqie Auliana, Hainur Fardatin (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: This study aims to see 1) knowledge concerning nutrition 2) knowledge concerning heart sickness and applying 13 message of base in everyday life mothers’ participant of active healthy heart club which have done effort operation of heart sickness risk.Method: Research type is survey with location research of Kalurahan Pleret District of Pleret Sub-Province of Bantul Yogyakarta. Population Research is homogen with housewife criterion have age 20-55 year with consideration of risk factor at woman happened age 55 year so that before age are they have prepared herself healthy life. Research Sample selected by simple sampling random counted 30 housewife people participant of active healthy heart club ( gymnastic group) and 30 housewife people is not participant of healthy heart club (not gymnastic group). Research data collected use 3 instruments that are knowledge test of nutrition, test knowledge of heart sickness and questioner applying 13 messages of PUGS. Validity and reliability instrument as data collectors with correlation product moment test and kruder-richardson technique.Result and conclusion: Result of research show 1) knowledge of nutrition between gymnastic group and not gymnastic group have difference 0,6. In gymnastic group 29 people is good and not gymnastic group 27 people is good, with mean assess gymnastic group 14,97 and not gymnastic group 14,37, meaning most researches sampel have owned knowledge of good gizi, 2) knowledge concerning heart sickness between group have difference 0,27, all sample have good knowledge of heart sickness with mean assess gymnastic group 13,75 and not gymnastic group 13,1, and 3) all sampel have good applied 13 message of base of PUGS better in everyday life, this matter for gymnastic group have as according to behavioral theory that good knowledge is basis for behavior.Keywords : PUGS, heart disease, SJS